DRS // CUMULUS Oslo 2013. The 2nd International Conference for Design Education Researchers - Nielsen, Liv Merete (FormAkademisk, 2012)
This international conference is a springboard for sharing ideas and concepts about contemporary design education research. Contributors are invited to submit research that deals with different facets of contemporary approaches to design education research. All papers will be double-blind peer-reviewed. This conference is open to research in any aspect and discipline of design education. Conference theme: Design Learning for Tomorrow - Design Education from Kindergarten to PhD